If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -1(2c + 3) = 2(c + 3) + c Reorder the terms: 29 + -1(3 + 2c) = 2(c + 3) + c 29 + (3 * -1 + 2c * -1) = 2(c + 3) + c 29 + (-3 + -2c) = 2(c + 3) + c Combine like terms: 29 + -3 = 26 26 + -2c = 2(c + 3) + c Reorder the terms: 26 + -2c = 2(3 + c) + c 26 + -2c = (3 * 2 + c * 2) + c 26 + -2c = (6 + 2c) + c Combine like terms: 2c + c = 3c 26 + -2c = 6 + 3c Solving 26 + -2c = 6 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 26 + -2c + -3c = 6 + 3c + -3c Combine like terms: -2c + -3c = -5c 26 + -5c = 6 + 3c + -3c Combine like terms: 3c + -3c = 0 26 + -5c = 6 + 0 26 + -5c = 6 Add '-26' to each side of the equation. 26 + -26 + -5c = 6 + -26 Combine like terms: 26 + -26 = 0 0 + -5c = 6 + -26 -5c = 6 + -26 Combine like terms: 6 + -26 = -20 -5c = -20 Divide each side by '-5'. c = 4 Simplifying c = 4
| p^2+2pq+q^2-2p-2q-15=0 | | 3(m+4)=39 | | 12+36x+27x^2=0 | | x-2x-25=0 | | t^4-7t^2-18=0 | | X=8+9Y-5*2 | | x=x+6 | | 60[100s]= | | 10x^2+21x-27=0 | | 28+x=24 | | 12d-6+4d= | | N+17=22 | | (y-2)-(Y+6)=4Y | | 19-A=3 | | 21=7S | | -380+x+x^2=0 | | 99-M=3 | | 7x-4-5x+2=10x+6-7x-4 | | a^2-18ab-40b^2= | | 2x^2-3x=35 | | 3(t-1)=qt | | -15=5b+12-2b | | 8a+20b=100 | | 99-M=72 | | a^2+17ab+72b^2= | | a^2+4ab-21b^2= | | 9n+45=10n-120 | | m^2+15m-100= | | m^2-15m-100= | | 3-46=10b+10 | | -33+4x=x | | m^2+25m+100= |